(untitled) (CIPEEX, 2022)
IT IS NOTED THAT THE DEVELOPMENT OF THE TECHNOLOGY MARKET IN RECENT YEARS HAS BEEN INCREASING, BEING DRIVEN BY THE COVID-19 PANDEMIC. THE REALITY IS THAT MORE AND MORE STARTUPS HAVE BEEN CREATED TO SOLVE VARIOUS PROBLEMS AND THESE STARTUPS NEED QUALIFIED PROFESSIONALS TO MEET THEIR DEMANDS.